Dr. Jure Žigon received the Jesenko Award of the Biotechnical Faculty UL for the best PhD graduate in 2021 - Dahle, Sebastian (Les (Ljubljana), 2022)
The Jesenko Awards of the Biotechnical Faculty, University of Ljubljana, are the highest awards for pedagogical, research and professional achievements and for economic and general social progress in the biotechnical field in Slovenia. The Biotechnical Faculty has been giving these awards since 1973, including the Jesenko Award for the best doctoral studies graduate. For 2021 the recipient of this award was Assist. Dr. Jure Žigon, who received it at a celebration in March 2022. Dr. Žigon is employed at the Department of Wood Science and Technology at the Biotechnical Faculty as an independent professional associate.
Keywords: biografije; Jesenkove nagrade; Oddelek za lesarstvo; Žigon, Jure